Uniformly Accelerating Charged Particles A Threat to the Equivalence Principle - Lyle, Stephen (Fundamental Theories of Physics, 2008)
There has been a long debate about whether uniformly accelerated charges should radiate electromagnetic energy and how one should describe their worldline through a flat spacetime, i.e., whether the Lorentz-Dirac equation is right. There are related questions in curved spacetimes, e.g., do different varieties of equivalence principle apply to charged particles, and can a static charge in a static spacetime radiate electromagnetic energy? The problems with the LD equation in flat spacetime are spelt out in some detail here, and its extension to curved spacetime is discussed. Different equivalence principles are compared and some vindicated. The key papers are discussed in detail and many of their conclusions are significantly revised by the present solution.